The Finite-Dimensional Uniform Attractors for the Nonautonomous g-Navier-Stokes Equations. (25th February 2009) - Wu, Delin
Abstract : We consider the uniform attractors for the two dimensional nonautonomous g-Navier-Stokes equations in bounded domainΩ . Assumingf = f ( x, t ) ∈ L loc 2, we establish the existence of the uniform attractor inL 2 ( Ω ) andD ( A 1 / 2 ) . The fractal dimension is estimated for the kernel sections of the uniform attractors obtained.